Repercussões cardiovasculares secundárias à doença e ao tratamento da leishmaniose visceral - Gomes, Marcos Couto (2019)
A thorough analysis of the cardiovascular repercussions of visceral leishmaniasis (VL) and therapeutic modalities. In order to evaluate cardiovascular complications VL cardiovascular complications, we conducted an open randomized clinical trial with 54 inpatients hospitalized patients diagnosed with VL at the University Hospital of the Federal University of Sergipe, during 24 months. Patients were randomly assigned to four groups of therapies (N-methyl glucamine antimoniate, amphotericin B deoxycholate, liposomal amphotericin B amphotericin B liposomal and the combination liposomal amphotericin B + N-methyl glucamine antimoniate,) and were followed for 21 days. By means of simple linear regression, the time trends of heart rate, arrhythmia index, and QTc interval were correlated with heart rate, arrhythmia index, and QTc QTc interval correlated with treated group and treatment time in days. There were no changes in CK and CK-MB values. When all patients were grouped, regardless of the therapeutic of therapeutic intervention, there was a tendency for arrhythmia to increase until day 14, with a reduction in this trend on day 21. In patients receiving liposomal amphotericin B liposomal amphotericin B, there was no change in the tendency to arrhythmia events. The frequency of patients with cardiac arrhythmia appeared to be higher in patients treated with Amphotericin B Deoxycholate. The most frequent electrocardiographic changes were first degree right bundle branch block first degree right bundle branch block (30.4%), sinus tachycardia (22.8%), and ventricular repolarization disorder ventricular repolarization disorder (16.4%). The QTc interval was observed to decrease when compared to consecutive days of treatment. There were no clinical, electrocardiographic, or laboratory signs consistent with laboratory signs consistent with serious cardiovascular side effects occurred in all four regimens. regimens